El coro de la iglesia del convento de San Agustín de Bogotá : culto divino y espacio coral en Santafé, 1675 – 1861 (2019)
The choir of San Agustín of Bogotá is a historical interior in excellent state of conservation; composed of wooden choir stalls and artistic works, arranged in harmony with the church where it is located. This choir is part of a typology almost disappeared nationwide: the urban cloister choir. It presents a rich and complex artistic program as well as distinctive techniques of its time of manufacture. This paper aims to provide arguments for its material conservation through a reflection on the problem of its obsolescence in the current liturgy. The church is located within the historic center of the city and so it is protected as cultural heritage of the nation since 1975. It was built by the Order of Saint Augustine between 1637 and 1668 (although it includes a ward from the 16th century). Its value as cultural heritage comes especially from its furniture and artwork. Even though the church has been intervened several times, its choir has not been modified. It is composed of 72 choir stalls in walnut wood, placed on the opposite end of the altar beneath a timber vaulted nave, above the church’s entry cancel. The artistic work -which forms a compositional unit with the choir stalls- dates from the same period (late sixteen hundreds to early eighteen hundreds), and consists of oil paintings on the high-backed seats and plaster sculptures fixed to the walls and the prioral seat. The only missing pieces are the choir lectern and the organ.